In vivo efficacy of melanoma internal radionuclide therapy with a 131I‐labelled melanin‐targeting heteroarylcarboxamide molecule. Issue 5 (18th March 2013) - Degoul, Françoise; Borel, Michèle; Jacquemot, Nathalie; Besse, Sophie; Communal, Yves; Mishellany, Florence; Papon, Janine; Penault‐Llorca, Frédérique; Donnarieix, Denise; Doly, Michel; Maigne, Lydia; Miot‐Noirault, Elisabeth; et al.
<x xml:space="preserve">Abstract</x> The development of alternative therapies for melanoma treatment is of great interest as long‐term tumour regression is not achieved with new targeted chemotherapies on selected patients. We previously demonstrated that radioiodinated heteroarylcarboxamide ([131I]ICF01012) induced a strong anti‐tumoural effect by inhibiting both primary tumour growth and dissemination process in a B16BL6 melanoma model. In our study, we show that a single injection of [131I]ICF01012 (ranging from 14.8 to 22.2 MBq) was effective and associated with low and transient haematological toxicity. Concerning pigmented organs, cutaneous melanocytes and skin were undamaged. In 30% of treated animals, no histological alteration of retina was observed, and in the remaining 70%, damages were restricted to the optic nerve area. Using the Medical Internal Radiation Dose methodology, we determined that the absorbed dose in major organs is very low (<4 Gy) and that a delivery of 30 Gy to the tumour is sufficient for an effective anti‐tumoural response. Molecular analyses of treated tumours showed a strong radiobiological effect with a decrease in proliferation, survival and pro‐angiogenic‐related markers and an increase in tumour suppressor gene expression, melanogenesis and anti‐angiogenic markers. All these features are in accordance with a tumour cell death mechanism that mainly occurs by mitotic catastrophe and provide a better understanding of in vivo anti‐tumoural effects of [131I] radionuclide. Our findings raise [131I]ICF01012 a good candidate for disseminated melanoma treatment and strongly support transfer of [131I]ICF01012 to clinical trial.